MANAGEMENT CONTROL SYSTEMSâ€™ LITERATURE DEVELOPMENT: THEORETICAL APPROACHES AND CRITIQUES WITHIN THE FUNCTIONALIST PARADIGM - Porporato, Marcela (Revista Universo Contábil, 2011)
This paper draws a simplified map of the evolution and current state of the theories and frameworks behind management accounting within the functionalist paradigm (PUXTY, 1993) as an aid for researchers and advanced business students. The study summarily presents the paradigms recognized in management accounting as a way to provide a better perspective of the field to novice researchers. Within the functionalist paradigm the evolution of management accounting literature is documented. The historical analysis, framed as a timeline, organizes the diverse research that has dominated the field since the beginning of 1900s in clusters around a certain theory or framework. The ten frameworks identified are: 1) conventional wisdom; 2) mathematical modeling; 3) systems; 4) Anthony’s framework; 5) behavioral; 6) human information processing; 7) transaction costs; 8) agency theory; 9) contingency theory; and 10) strategic. The transition from one cluster of theory or framework to another is explained by critiques; however, some theories and frameworks evolved naturally into others without the need of a critique.